Rank based Approach for Extracting Unit Pixel Width Skeleton. Issue 3 (December 2020) - Neelima, N.; Srikrishna, Dr. A.; Gangadhara Rao, Dr. K.
Abstract: Skeletonization is a transformation of a digital picture component into a subset of the original component. The skeleton is a qualitative tool for matching and analyzing 2D objects. Skeletonization is considered as an important issue because of the close link between an object's skeleton and its boundary. Arank based skeleton extraction algorithm is presented which iterates itself to remove all the skeleton branches corresponding to the unimportant shape regions depending on the boundary extraction method. The method proposed performance is compared with various methods in the literature such as ZS, LW, and MZS skeletonization algorithms and identified that proposed method out performs well with respect to the performance measures elapsed time, thinning rate, thinning speed, and connectivity.